Titanium-based catalyst, preparation method of titanium-based catalyst and synthesis method of pyroxasulfone
By using a titanium-based catalyst, which consists of aerobic vacancies defective titanium dioxide nanoribbons and additive metal component M, the problem of high cost and low reaction efficiency in the synthesis of sulfonpyrazole is solved, and efficient and continuous sulfonpyrazole synthesis is achieved.
Patent Information
- Application Number
- CN202510123722.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-26
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2045-01-26
AI Technical Summary
The existing tungsten, molybdenum or niobium catalysts have high costs in the synthesis of sulfonpyrazole, inability to achieve continuous production, long reaction cycles, high post-treatment costs, slow reaction kinetics, difficulty in long-term production in fixed beds, poor catalytic activity, and low reaction selectivity.
A titanium-based catalyst is used, which consists of a titanium dioxide nanoribbon forming an aerobic vacancies defect as the main active component, and dopant additive metal components M such as Re, Ru, Mo, V, Ce, Zn and Cr, and forms Ti3+-Vo-Ti3+ surface defect sites through a specific preparation method to improve the activity and selectivity of the catalyst.
The efficient synthesis of sulfonopyrazole was achieved, the raw material conversion rate reached 100%, the product selectivity was high, and the continuous production of sulfonopyrazole was achieved, reducing production costs.
Smart Images

Figure CN119549147A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical industry, and in particular to a titanium-based catalyst and a preparation method thereof, and a synthesis method of sulfonepyraclostrobin. Background Art
[0002] Pyroxasulfone, molecular formula: C 12 H 14 F 5 N 3 O 4 S, molecular weight: 391.31, chemical name: 3-[(5-difluoromethoxy-1-methyl-3-trifluoromethylpyrazol-4-yl)-methylsulfonyl]-4,5-dihydro-5,5-dimethyl-1,2-isoxazole, the compound structure is as follows:
[0003]
[0004] Sulfonepyraclostrobin is an isoxazole herbicide that inhibits plant cell division. The herbicide was first discovered by the KI Chemical Research Institute in Japan, and later industrialized by Kumizu Chemical Co., Ltd. and Ibara Chemical Co., Ltd. in Japan. Sulfonepyraclostrobin is a broad-spectrum herbicide that can be used as a pre-emergence soil treatment agent in most crop fields. Its mechanism of action is similar to that of acetochlor and isopropylamine herbicides. After application, it is absorbed by the young roots and shoots of weeds, inhibiting the early growth of seedlings, destroying meristems and coleoptiles, and is a serious potential inhibitor of the biosynthesis of VLCFA (very long side chain fatty acids) (C20-C30) in plants. It has the advantages of high biological activity, low application rate per unit area, and long weed control period.
[0005] The synthesis of sulfone pyraclostrobin involves multiple steps, among which the oxidation of sulfide to sulfone is the key step of the reaction, and is also a hot spot and difficulty in research. Currently, the selective oxidation of sulfide to sulfone is usually carried out in a batch reactor using a homogeneous tungsten catalyst or a molybdenum catalyst, which is often accompanied by the production of by-products sulfoxide and peroxidation impurities. Among them, how to control the high selectivity of sulfide oxidation to sulfone is the key point of the synthesis of this reaction.
[0006] The existing catalysts for the oxidation of sulfide (3-[(5-difluoromethoxy-1-methyl-3-trifluoromethylpyrazol-4-yl)-methylthio]-4,5-dihydro-5,5-dimethyl-1,2-isoxazole) to sulfonepyrazol are mainly concentrated in tungsten, molybdenum or niobium catalysts, especially tungsten catalysts (such as tungstic acid, tungstates (sodium tungstate, sodium tungstate dihydrate, etc.), tungsten oxide, phosphotungstic acid and its salts, etc.), but such catalysts have the following problems: 1. Tungsten, molybdenum and niobium catalysts are expensive (especially tungsten and niobium catalysts) and the existing technology can only be used for batch reactor oxidation reaction, without continuous reaction. 1. The conditions for the continuous production of sulfonepyraclostrobin; 2. The batch reaction cycle is long, the catalyst recovery is difficult, the active components are easy to lose and difficult to reuse, the catalyst use cost is high and the product separation and purification increases the additional investment; 3. Most of the existing catalysts are bulk structures with large particle sizes, small numbers of exposed active metal atoms, and low catalyst active surface areas, which are not conducive to the adsorption and activation of reactants, resulting in slow kinetics of sulfide oxidation reactions; 4. The reaction system generally contains acidic substances such as sulfuric acid and hydrochloric acid, and general supported catalysts (such as alumina as a carrier) are difficult to meet the requirements of long-term fixed bed production.
[0007] In view of this, this application is hereby filed. Summary of the invention
[0008] The main purpose of the present invention is to provide a titanium-based catalyst and a preparation method thereof and a method for synthesizing sulfonepyraclostrobin, so as to solve at least one of the problems of using tungsten catalyst, molybdenum catalyst or niobium catalyst as a catalyst for synthesizing sulfonepyraclostrobin in the prior art, such as high cost, inability to continuously produce sulfonepyraclostrobin, long reaction cycle, high post-processing cost, slow reaction kinetics, difficulty in long-term production in a fixed bed, poor catalytic activity and low reaction selectivity.
[0009] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a titanium-based catalyst is provided, comprising: a main active component and an auxiliary metal component M doped in the main active component; wherein the main active component is a titanium dioxide nanobelt, and the titanium dioxide nanobelt forms oxygen vacancy defects, and the concentration of the oxygen vacancy defects is 5~20μmol / g; the auxiliary metal component M comprises at least one of Re, Ru, Mo, V, Ce, Zn and Cr.
[0010] Furthermore, the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelt is 0.5~5:100.
[0011] Furthermore, the titanium dioxide nanobelt is in the shape of a nanobelt, and its thickness is 1 to 5 nm.
[0012] According to another aspect of the present invention, a method for preparing the titanium-based catalyst provided in the first aspect is provided, and the preparation method comprises the following steps: step S1, preparing titanium dioxide nanobelts with oxygen vacancy defects; step S2, mixing the titanium dioxide nanobelts, M source and water, and then sequentially performing a first drying and a first calcination to obtain a titanium-based catalyst.
[0013] Furthermore, step S1 includes: step S11, mixing a titanium source with an alkaline solution, conducting a hydrothermal reaction, and obtaining titanate; step S12, mixing titanate, alcohol, and an acidic solution for ion exchange, and obtaining titanate nanobelts; step S13, sequentially washing and second drying the titanate nanobelts, and obtaining a titanium dioxide nanobelt precursor; step S14, conducting a second calcination on the titanium dioxide nanobelt precursor, and obtaining titanium dioxide nanobelts.
[0014] Further, in step S11, the titanium source is at least one of titanium dioxide, titanyl sulfate and P25 titanium dioxide;
[0015] and / or, the alkaline solution comprises sodium hydroxide solution and / or potassium hydroxide solution;
[0016] and / or, the concentration of the alkaline solution is 1 to 20 mol / L, further 6 to 12 mol / L;
[0017] and / or, the molar ratio of the titanium source to the alkaline solution is 1:2-50, further 1:10-20;
[0018] And / or, the temperature of the hydrothermal reaction is 120-200° C., and the time of the hydrothermal reaction is 12-96 hours.
[0019] Further, in step S12, the concentration of the acidic solution is 0.01-5 mol / L;
[0020] and / or, the acidic solution comprises a hydrochloric acid solution and / or a nitric acid solution;
[0021] and / or, the alcohol is at least one of aromatic alcohols having 6 to 15 carbon atoms;
[0022] And / or, the molar ratio of alcohol to titanium source is 0.1-10:1.
[0023] Further, in step S14, the second calcination includes first performing oxygen-containing calcination in an oxygen-containing atmosphere and then performing inert calcination in an inert atmosphere.
[0024] Further, the oxygen-containing atmosphere includes air and / or oxygen.
[0025] Furthermore, the temperature of oxygen-containing calcination is 200-450° C., and the time of oxygen-containing calcination is 1-4 hours.
[0026] Further, the inert atmosphere includes at least one of argon and / or nitrogen.
[0027] Furthermore, the temperature of the inert calcination is 500-700° C., and the time of the inert calcination is 2-6 hours.
[0028] Furthermore, in step S2, the temperature of the first calcination is 300-600°C, and the time of the first calcination is 2-4 hours.
[0029] Further, the M source includes at least one of a Re source, a Ru source, a Mo source, a V source, a Ce source, a Zn source and a Cr source; wherein the Re source is selected from at least one of rhenium chloride, perrhenic acid and ammonium perrhenate; the Ru source is selected from ruthenium chloride and / or ruthenium acetate; the Mo source is selected from at least one of ammonium molybdate tetrahydrate, molybdenum chloride, phosphomolybdic acid and ammonium phosphomolybdate; the V source is selected from ammonium metavanadate and / or vanadium trichloride; the Ce source is selected from at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate; the Zn source is selected from at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; the Cr source is selected from at least one of chromium nitrate, chromium sulfate and chromium acetate.
[0030] According to the third aspect of the present invention, a method for synthesizing sulfonepyraclostrobin is provided, the method comprising: an oxidation reaction of a sulfide intermediate of formula (A) with hydrogen peroxide under the action of a catalyst to obtain sulfonepyraclostrobin. The synthesis diagram of sulfonepyraclostrobin is as follows:
[0031]
[0032] Wherein, the catalyst is the titanium-based catalyst provided in the first aspect or the titanium-based catalyst obtained by the preparation method provided in the second aspect.
[0033] Furthermore, the catalyst is loaded in a fixed bed, and the temperature of the oxidation reaction is 45-60°C.
[0034] Applying the technical solution of the present invention, the titanium-based catalyst provided by the present application forms oxygen vacancy defects (V o ) is the main active component, and the titanium dioxide nanobelt is doped with an auxiliary metal component M. Due to the loss of lattice oxygen in the titanium dioxide nanobelt, part of the tetravalent Ti 4+ Reducing to Ti 3+ , adjacent Ti 3+ With oxygen vacancies (V o ) formed between Ti 3+ -V o -Ti 3+ Surface defect sites. The titanium dioxide nanobelt has a large specific surface area and fully exposed active sites. In the reaction of sulfide oxidation to synthesize sulfone pyraclostrobin, the unsaturated Ti 3+ -Vo -Ti 3+ Surface defect sites can enhance the adsorption and activation of reactants, and the adjacent Ti 3+ It can form stable Ti with sulfide and hydrogen peroxide 3+ -S-Ti 3+ and Ti 3+ -O-Ti 3+ The titanium dioxide nanobelts have good wettability and ductility, which helps the diffusion and transport of reactant molecules, thereby increasing the reaction rate.
[0035] In addition, due to Ti 3+ -V o -Ti 3+ Surface defect sites have higher energy, oxygen vacancies (V o ) can interact with the additive metal ions electronically, through Ti 3+ -V o -Ti 3+ The electron positioning center formed by the surface defect sites anchors the auxiliary metal component M, improves the dispersibility and stability of the auxiliary metal component M on the titanium dioxide nanobelts, and thus provides more reaction active sites. At the same time, it also extends the service life of the titanium-based catalyst, which is beneficial to the efficient and stable oxidation of sulfide to sulfone in the reaction.
[0036] The titanium-based catalyst provided in the present application, in the reaction of using a fixed bed to oxidize a sulfide intermediate to synthesize sulfonepyraclostrobin, can achieve a raw material conversion rate of 100%, a high product selectivity, and also realize the continuous production of sulfonepyraclostrobin. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0038] Figure 1 The SEM image of the titanium dioxide nanobelt prepared in Example 1 of the present invention is shown;
[0039] Figure 2 The TEM image of the titanium dioxide nanobelt prepared in Example 1 of the present invention is shown. DETAILED DESCRIPTION
[0040] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0041] As analyzed in the background technology of this application, the prior art tungsten catalyst, molybdenum catalyst or niobium catalyst as a catalyst for synthesizing sulfonepyraclostrobin has at least one of the following problems: high cost, inability to continuously produce sulfonepyraclostrobin, long reaction cycle, high post-processing cost, slow reaction kinetics, difficulty in long-term production in a fixed bed, poor catalytic activity, and low reaction selectivity. In order to solve this problem, the present application provides a titanium-based catalyst and a preparation method thereof and a synthesis method of sulfonepyraclostrobin.
[0042] In a typical embodiment of the present application, a titanium-based catalyst is provided, characterized in that it comprises: a main active component and an auxiliary metal component M doped in the main active component; wherein the main active component is a titanium dioxide nanobelt, the titanium dioxide nanobelt forms oxygen vacancy defects, and the concentration of oxygen vacancy defects is 5~20μmol / g; the auxiliary metal component M comprises at least one of Re, Ru, Mo, V, Ce, Zn and Cr.
[0043] The titanium-based catalyst provided in the present application is used to form oxygen vacancy defects (V o ) is the main active component, and the titanium dioxide nanobelt is doped with an auxiliary metal component M. Due to the loss of lattice oxygen in the titanium dioxide nanobelt, part of the tetravalent Ti 4+ Reducing to Ti 3+ , adjacent Ti 3+ With oxygen vacancies (V o ) formed between Ti 3+ -V o -Ti 3+ Surface defect sites. The titanium dioxide nanobelt has a large specific surface area and fully exposed active sites. In the reaction of sulfide oxidation to synthesize sulfone pyraclostrobin, the unsaturated Ti 3+ -V o -Ti 3+ Surface defect sites can enhance the adsorption and activation of reactants, and the adjacent Ti 3+ It can form stable Ti with sulfide and hydrogen peroxide 3+ -S-Ti 3+ and Ti 3+ -O-Ti 3+ The titanium dioxide nanobelts have good wettability and ductility, which helps the diffusion and transport of reactant molecules, thereby increasing the reaction rate.
[0044] In addition, due to Ti 3+ -V o -Ti 3+ Surface defect sites have higher energy, oxygen vacancies (V o ) can interact with the additive metal ions electronically, through Ti 3+-V o -Ti 3+ The electron positioning center formed by the defect site anchors the auxiliary metal component M, improves the dispersibility and stability of the auxiliary metal component M on the titanium dioxide nanobelts, and then provides more reaction active sites. At the same time, it also prolongs the service life of the titanium-based catalyst, which is beneficial to the efficient and stable oxidation of sulfide to sulfone in the reaction.
[0045] The titanium-based catalyst provided in the present application, in the reaction of sulfide oxidation to synthesize sulfonepyraclostrobin in a fixed bed, can achieve a raw material conversion rate of 100%, a high product selectivity, and also realize the continuous production of sulfonepyraclostrobin.
[0046] In the present application, the concentration of oxygen vacancy defects being "5 to 20 μmol / g" means that 1 g of titanium dioxide nanobelt contains 5 to 20 μmol of oxygen vacancy defects.
[0047] Typically, but not limitatively, the concentration of oxygen vacancy defects in the titanium dioxide nanobelts provided in the present application is 5 μmol / g, 5.03 μmol / g, 7.27 μmol / g, 8.69 μmol / g, 10 μmol / g, 11.36 μmol / g, 13.07 μmol / g, 13.52 μmol / g, 15 μmol / g, 15.38 μmol / g, 16.21 μmol / g, 19.61 μmol / g, 20 μmol / g or a range consisting of any two values.
[0048] In order to further improve the conversion rate and product selectivity of sulfide oxidation to sulfonepyraclostrobin, the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelts in the titanium-based catalyst is preferably 0.5~5:100.
[0049] In the present application, the auxiliary metal component M can be any one or more of Re, Ru, Mo, V, Ce, Zn and Cr. When the auxiliary metal component M is Re, the mass ratio of Re to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is Ru, the mass ratio of Ru to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is Mo, the mass ratio of Mo to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is V, the mass ratio of V to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is Ce, the mass ratio of Ce to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is Zn, the mass ratio of Zn to titanium dioxide nanobelt is 0.5~5:100; when the auxiliary metal component M is Cr, the mass ratio of Cr to titanium dioxide nanobelt is 0.5~5:100.
[0050] When the auxiliary metal component M is any two of Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of the two auxiliary metal components to the mass of the titanium dioxide nanobelt is 0.5~5:100, and the two auxiliary metal components are Re and Ru; Ru and Mo; Mo and V; V and Ce; Ce and Zn; Zn and Cr, etc.
[0051] When the auxiliary metal component M is any three of Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of the three auxiliary metal components to the mass of the titanium dioxide nanobelts is 0.5~5:100, and the three auxiliary metal components are Re, Ru and Mo; Re, Ce and V; Ce, Zn and Cr; Mo, Zn and V; Re, Cr and V; Ru, Cr and Zn, etc.
[0052] When the auxiliary metal component M is any four of Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of the four auxiliary metal components to the mass of the titanium dioxide nanobelts is 0.5~5:100, and the four auxiliary metal components are Re, Ru, Mo and V; Re, Ru, Mo, and Ce; V, Ce, Zn and Cr, etc.
[0053] When the auxiliary metal component M is any five of Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of the five auxiliary metal components to the mass of the titanium dioxide nanobelts is 0.5~5:100. The five auxiliary metal components are Re, Ru, Mo, V and Ce; Re, Ru, Mo, V and Zn; Re, Ru, Mo, V and Cr, etc.
[0054] When the auxiliary metal component M is any six of Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of the six auxiliary metal components to the mass of the titanium dioxide nanobelts is 0.5~5:100. The six auxiliary metal components are Re, Ru, Mo, V, Ce and Zn; Re, Ru, Mo, V, Ce and Cr, etc.
[0055] When the auxiliary metal component M is Re, Ru, Mo, V, Ce, Zn and Cr, the mass ratio of the total mass of these seven auxiliary metal components to the mass of the titanium dioxide nanobelts is 0.5~5:100.
[0056] Typically but not limitatively, in the titanium-based catalyst provided in the present application, the mass ratio of the auxiliary metal active component M to the titanium dioxide nanobelt is 0.5:100, 1:100, 2:100, 3:100, 4:100, 5:100 or a range consisting of any two values.
[0057] In order to further increase the specific surface area of the catalyst, increase the number of exposed active metal atoms, and further improve the adsorption and activation of reactants, and improve the reaction kinetics of the sulfide oxidation process, the titanium dioxide nanobelt is preferably in the shape of a nanobelt with a thickness of 1 to 5 nm.
[0058] Typically but not limiting, the thickness of the titanium dioxide nanoribbon is 1 nm, 2 nm, 3 nm, 4 nm, 5 nm, or a range consisting of any two of these values.
[0059] In order to facilitate the continuous synthesis of sulfonepyraclostrobin by loading the titanium-based catalyst provided in the present application into a fixed bed, in some embodiments, the titanium-based catalyst provided in the present application is granular, and its average particle size is 20-40 mesh, such as 20 mesh, 25 mesh, 30 mesh, 35 mesh, 40 mesh or a range value composed of any two numerical values.
[0060] In another typical embodiment of the present application, a method for preparing the titanium-based catalyst provided in the first typical embodiment is provided, comprising the following steps: step S1, preparing titanium dioxide nanobelts with oxygen vacancy defects; step S2, mixing the titanium dioxide nanobelts, M source and water, and then sequentially performing a first drying and a first calcination to obtain a titanium-based catalyst.
[0061] In the present invention, the titanium dioxide nanobelt with oxygen vacancy defects, the M source and water are first mixed and uniformly dispersed. 3+ -V o -Ti 3+ Surface defect sites have higher energy, oxygen vacancies (V o ) can interact with metal ions in the M source through Ti 3+ -V o -Ti 3+ The electron localization center formed by the defect site anchors the metal ions in the M source, thereby improving the dispersibility and stability of the M source on the titanium dioxide nanobelt. In addition, the titanium dioxide nanobelt has good wettability and ductility, which is helpful for the molding of the titanium-based catalyst. The titanium-based catalyst can be obtained by drying and removing the solvent once and then calcining once. The preparation method provided in the present application has low preparation cost, simple operation, and can realize the continuous production of sulfonepyraclostrobin on a fixed bed.
[0062] In some embodiments, the above-mentioned step S1 includes: step S11, mixing a titanium source with an alkaline solution, conducting a hydrothermal reaction, and obtaining titanate; step S12, mixing titanate, alcohol, and an acidic solution for ion exchange to obtain titanate nanobelts; step S13, washing the titanate nanobelts in sequence, and performing a second drying to obtain a titanium dioxide nanobelt precursor; step S14, performing a second calcination on the titanium dioxide nanobelt precursor to obtain titanium dioxide nanobelts.
[0063] The present invention uses a titanium source as a raw material, firstly subjecting the titanium source to a hydrothermal reaction under alkaline conditions, so that the titanium source reacts with an alkaline solution to obtain a titanate. Subsequently, the obtained titanate is mixed with an alcohol and an acidic solution for ion exchange, and the titanate reacts with the H in the acidic solution. + The titanium oxide nanobelts were washed to remove the residual H + The solvent is removed by a second drying to obtain a titanium dioxide nanobelt precursor. The alcohol organic matter adsorbed on the surface of the titanium dioxide nanobelt precursor is then decomposed by a second calcination to consume lattice oxygen, thereby forming oxygen vacancy defects (V o In addition, titanate nanoribbons have the structural properties of two-dimensional materials. Under high-temperature calcination conditions, their surface atoms can escape from the lattice to form oxygen vacancy defects (V o ). Due to the loss of lattice oxygen, part of the tetravalent Ti 4+ Reducing to Ti 3+ , adjacent Ti 3+ With oxygen vacancies (V o ) formed between Ti 3+ -V o -Ti 3+ Surface defect sites are formed, thereby obtaining a titanium dioxide nanobelt with oxygen vacancy defects, and the thickness of the titanium dioxide nanobelt is relatively thin, which further promotes the escape of surface atoms from the lattice to form oxygen vacancy defects (V o ).
[0064] In the above step S11, in order to further promote the formation of titanate, the titanium source is preferably any one or more of titanium dioxide, titanyl sulfate and P25 titanium dioxide.
[0065] In order to further increase the rate of the hydrothermal reaction of the titanium source under alkaline conditions to generate titanate, the concentration of the alkaline solution is preferably 1-20 mol / L, more preferably 6-12 mol / L. It is further preferred that the alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution.
[0066] Typically, but not limiting, the concentration of the alkaline solution is preferably 1 mol / L, 6 mol / L, 10 mol / L, 12 mol / L, 16 mol / L, 20 mol / L or a range consisting of any two values.
[0067] In order to further ensure the completeness and selectivity of the hydrothermal reaction and to further improve the yield and purity of the titanate, the molar ratio of the titanium source to the alkaline solution is preferably 1:2-50, and more preferably 1:10-20.
[0068] Typically but not limiting, the molar ratio of the titanium source to the alkaline solution is 1:2, 1:6, 1:10, 1:15, 1:20, 1:30, 1:40, 1:50 or a range consisting of any two values.
[0069] In order to further improve the rate of the hydrothermal reaction and the yield of titanate, the hydrothermal reaction temperature is preferably 120~200°C, and the hydrothermal reaction time is 12~96h; the hydrothermal reaction temperature is further preferably 150~180°C, and the hydrothermal reaction time is 36~72h.
[0070] Typically but not limiting, the temperature of the hydrothermal reaction is 120°C, 140°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 190°C, 200°C or a range consisting of any two values; the time of the hydrothermal reaction is 12h, 24h, 36h, 42h, 48h, 54h, 60h, 66h, 72h, 84h, 96h or a range consisting of any two values.
[0071] In the above step S12, since the concentration of hydrogen ions in the ion exchange process will affect the growth and formation process of titanate nanobelts, in order to further control the morphology, structure and properties of titanate nanobelts, the concentration of the acidic solution is preferably 0.01~5 mol / L; and the acidic solution is further preferably composed of hydrochloric acid solution and / or nitric acid solution.
[0072] Typically but not limiting, the concentration of the acidic solution is 0.01 mol / L, 0.05 mol / L, 0.1 mol / L, 0.5 mol / L, 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L or a range consisting of any two values.
[0073] In order to further promote the formation of titanate nanobelts, the alcohol is preferably any one or more of aromatic alcohols having carbon atoms of 6 to 15. Aromatic alcohols have strong coordination and complexing ability and stability, and under the action of aromatic groups and hydrophobicity, are more conducive to interacting with titanate to form a titanate layered structure, and finally form a titanate nanobelt structure.
[0074] In order to further increase the content of alcohol organic matter adsorbed on the surface of titanate nanobelts, and further increase the oxygen vacancy defects (V o The molar ratio of alcohol to titanium source is preferably 0.1 to 10:1.
[0075] Typically but not limiting, the molar ratio of alcohol to titanium source is 0.1:1, 0.5:1, 1:1, 2:1, 4:1, 6:1, 8:1, 10:1 or a range consisting of any two of these values.
[0076] In order to further improve the mixing uniformity of the titanate, alcohol and acid solution in step S12, the mixing method is preferably stirring, and the stirring time is further preferably 1 to 6 hours.
[0077] In the above step S13, in order to further ensure that the residual H + To remove, preferably use deionized water for washing, and wash the titanate nanobelts to a pH of 4-7 before performing subsequent steps, such as 4, 5, 6, 7 or a range of any two values.
[0078] In the above step S13, in order to further promote the drying of the titanate nanobelts, the washed titanate nanobelts are preferably first filtered and then dried overnight, and the second drying temperature is more preferably 60-120°C.
[0079] In some embodiments, in step S14, the second calcination includes first performing oxygen-containing calcination in an oxygen-containing atmosphere and then performing inert calcination in an inert atmosphere. The oxygen-containing calcination is first performed in an oxygen-containing atmosphere to promote the decomposition of alcohol organic matter adsorbed on the surface of the titanate nanobelts to consume lattice oxygen, thereby forming oxygen vacancy defects (V o ) is then calcined in an inert atmosphere to promote the escape of surface atoms of the titanate nanobelts from the lattice to form oxygen vacancy defects (V o ) . Calcination under two different atmosphere conditions can further promote oxygen vacancy defects (V o )’s formation.
[0080] In order to further increase the consumption of lattice oxygen by decomposition of alcohol organic matter, the oxygen-containing atmosphere preferably includes air and / or oxygen; the temperature of oxygen-containing calcination is preferably 200-450°C, and the time of oxygen-containing calcination is preferably 1-4h; further preferably, the temperature of oxygen-containing calcination is 300-400°C, and the time of oxygen-containing calcination is preferably 2-3h; the heating rate of oxygen-containing calcination is preferably 5-15°C / min.
[0081] Typically but not limiting, the temperature of oxygen-containing calcination is 200°C, 300°C, 350°C, 400°C, 450°C or a range consisting of any two values; the time of oxygen-containing calcination is 1h, 2h, 3h, 4h or a range consisting of any two values; the heating rate of oxygen-containing calcination is 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min or a range consisting of any two values.
[0082] In order to further promote the escape of surface atoms of titanate nanobelts from the lattice to form oxygen vacancy defects, the inert atmosphere is preferably argon and / or nitrogen; the inert calcination temperature is preferably 500-700°C, and the inert calcination time is preferably 2-6 hours; the inert calcination temperature is further preferably 600-650°C, and the inert calcination time is preferably 3-4 hours; the heating rate of the inert calcination is preferably 5-15°C / min.
[0083] Typically but not limiting, the temperature of the inert calcination is 500°C, 550°C, 600°C, 650°C, 700°C or a range consisting of any two values; the time of the inert calcination is 2h, 3h, 4h, 5h, 6h or a range consisting of any two values; the heating rate of the inert calcination is 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min or a range consisting of any two values.
[0084] In the above step S2, in order to further promote uniform mixing and dispersion of the titanium dioxide nanobelts and the M source in water, the mixing method is preferably ultrasonic dispersion, and the ultrasonic dispersion time is preferably 1 to 2 hours.
[0085] In the above step S2, in order to further increase the rate of solvent removal, the first drying temperature is preferably 80-100°C.
[0086] The above-mentioned M source includes any one or more of a Re source, a Ru source, a Mo source, a V source, a Ce source, a Zn source and a Cr source; wherein the Re source includes but is not limited to any one or more of rhenium chloride, perrhenic acid and ammonium perrhenate, and is further preferably rhenium chloride; the Ru source includes but is not limited to ruthenium chloride and / or ruthenium acetate, and is preferably ruthenium chloride; the Mo source includes but is not limited to any one or more of ammonium molybdate tetrahydrate, molybdenum chloride, phosphomolybdic acid and ammonium phosphomolybdate, and is further preferably ammonium molybdate tetrahydrate; the V source includes but is not limited to ammonium metavanadate and / or vanadium trichloride, and is further preferably ammonium metavanadate; the Ce source includes but is not limited to any one or more of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate, and is further preferably cerium nitrate; the Zn source includes but is not limited to any one or more of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate, and is further preferably zinc nitrate; the Cr source includes but is not limited to any one or more of chromium nitrate, chromium sulfate and chromium acetate, and is further preferably chromium nitrate.
[0087] In the above step S2, in order to further strengthen the bond between the metal ions in the M source and the titanium dioxide nanobelts and further improve the stability and activity of the catalyst, the temperature of the first calcination is preferably 300-600°C and the time of the first calcination is 2-4 hours. In order to further promote production efficiency and catalyst stability, the heating rate of the first calcination is preferably 5-15°C / min, and the atmosphere of the first calcination is preferably an oxygen-containing atmosphere or an inert atmosphere.
[0088] Typically but not limiting, the temperature of the first calcination is 300°C, 400°C, 500°C, 600°C or a range consisting of any two values; the time of the first calcination is 2h, 2.5h, 3h, 3.5h, 4h or a range consisting of any two values; the heating rate of the first calcination is 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min or a range consisting of any two values.
[0089] In some embodiments, in order to facilitate loading the titanium-based catalyst into a fixed bed for continuous synthesis of pyraclostrobin, the step S2 further includes tableting and crushing the titanium-based catalyst in sequence to obtain a titanium-based catalyst with an average particle size of 20-40 mesh.
[0090] In a third typical embodiment of the present application, a method for synthesizing sulfonepyraclostrobin is also provided, the method comprising: subjecting a sulfide intermediate to an oxidation reaction with hydrogen peroxide in the presence of a catalyst to obtain sulfonepyraclostrobin, wherein the synthesis schematic diagram of the sulfonepyraclostrobin is as follows:
[0091]
[0092] The above-mentioned catalyst is the titanium-based catalyst provided in the above-mentioned first typical embodiment or the titanium-based catalyst obtained according to the preparation method provided in the above-mentioned second typical embodiment.
[0093] The synthesis method of sulfonepyraclostrobin provided in the present application is to load the above catalyst on a fixed bed, so that the sulfide intermediate and hydrogen peroxide are continuously synthesized into sulfonepyraclostrobin in the fixed bed under the catalytic action of the catalyst. The raw material conversion rate reaches 100%, the product selectivity is high, and the production cost is reduced.
[0094] In addition, the present application adopts the oxygen vacancy defect (V o ) is the main active component, and the titanium dioxide nanobelt is doped with an auxiliary metal active component M. The titanium dioxide nanobelt is in the shape of a nanobelt, has a large specific surface area, fully exposed active sites, good wettability and ductility, and improves the reaction kinetics and reaction rate of the oxidation process in the reaction of sulfide oxidation to synthesize sulfonepyraclostrobin. 3+ -Vo -Ti 3+ The electron positioning center formed by the defect site anchors the dispersion auxiliary metal component M, improves the dispersibility and stability of the auxiliary metal component M on the titanium dioxide nanobelts, and then provides more reaction active sites, thereby improving the reaction activity; at the same time, it also extends the service life of the catalyst, thereby reducing the cost of catalyst use.
[0095] In some embodiments, the temperature of the oxidation reaction is 45-60°C, the reaction is mild, and it is more conducive to process control. The catalyst is loaded in a fixed bed and can be used continuously.
[0096] In some specific embodiments, when a fixed bed is used for the continuous preparation of sulfonepyraclostrobin, an acetonitrile solution of a thioether intermediate (the mass ratio of acetonitrile to the thioether intermediate is 3:1) with a flow rate of 0.5 g / min is passed into the fixed bed, and a hydrogen peroxide solution (mass concentration of 50 wt%) with a flow rate of 0.1 g / min is passed into the fixed bed for reaction.
[0097] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0098] Example 1
[0099] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component, and the titanium dioxide nanobelts are doped with auxiliary agents rhenium, auxiliary agent ruthenium and auxiliary agent molybdenum, and the mass ratio of the auxiliary agent rhenium to the titanium dioxide nanobelts is 0.5:100, the mass ratio of the auxiliary agent ruthenium to the titanium dioxide nanobelts is 1:100, and the mass ratio of the auxiliary agent molybdenum to the titanium dioxide nanobelts is 2:100.
[0100] The titanium-based catalyst preparation method comprises the following steps:
[0101] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0102] (1.1) 0.2 mol of P25 titanium dioxide powder was mixed with 500 mL of 8 M NaOH solution, and the mixture was transferred to a hydrothermal kettle with an inner liner. The hydrothermal kettle was placed in an oven and heated at 160 °C for 36 h for hydrothermal reaction. After the hydrothermal reaction was completed, the residual NaOH solution was removed by filtration to obtain a white sodium titanate solid.
[0103] (1.2) Add the white sodium titanate solid to a 1M HCl solution containing 0.5 mol 2-phenylisopropanol and stir for 3 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0104] (1.3) washing the titanate nanobelts with deionized water until the pH value is 5, then filtering, and then drying in an oven at 80°C to obtain a titanium dioxide nanobelt precursor;
[0105] (1.4) calcining the titanium dioxide nanobelt precursor at 350°C in air at a heating rate of 5°C / min for 3 h; then changing the calcination atmosphere to argon and calcining at 600°C in argon at a heating rate of 5°C / min for 4 h; after calcination, naturally cooling to room temperature to obtain titanium dioxide nanobelts;
[0106] (2) Add rhenium chloride, ruthenium chloride and ammonium molybdate tetrahydrate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of rhenium to titanium dioxide nanobelts is 0.5:100 based on rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 1:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 2:100 based on molybdenum in ammonium molybdate tetrahydrate. Ultrasonic dispersion for 1 hour, then evaporate and remove the solvent at 85°C to obtain a dry solid. The dry solid is heated to 450°C in air at a heating rate of 5°C / min and calcined for 3 hours to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0107] Example 2
[0108] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component. The titanium dioxide nanobelts are doped with auxiliary agents rhenium, auxiliary agent cerium and auxiliary agent vanadium, and the mass ratio of the auxiliary agent rhenium to the titanium dioxide nanobelts is 0.5:100, the mass ratio of the auxiliary agent cerium to the titanium dioxide nanobelts is 1:100, and the mass ratio of the auxiliary agent vanadium to the titanium dioxide nanobelts is 2:100.
[0109] The titanium-based catalyst preparation method comprises the following steps:
[0110] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0111] (1.1) Mix 0.2 mol of P25 titanium dioxide powder and 500 mL of 12 M NaOH solution, transfer to a hydrothermal kettle with a liner, place the hydrothermal kettle in an oven, and heat at 170 °C for 48 h. After the hydrothermal reaction is completed, filter out the residual NaOH solution to obtain a white sodium titanate solid.
[0112] (1.2) Add the white sodium titanate solid to 5M HNO containing 1 mol of o-cresol. 3The solution was stirred for 1 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0113] (1.3) washing the titanate nanobelts with deionized water until the pH value is 7, then filtering, and then drying in an oven at 90°C to obtain a titanium dioxide nanobelt precursor;
[0114] (1.4) The titanium dioxide nanobelt precursor was calcined in air at 450°C for 3 h at a heating rate of 10°C / min; then the calcination atmosphere was changed to argon and calcined in argon at 700°C for 2 h at a heating rate of 5°C / min; after calcination, the precursor was naturally cooled to room temperature to obtain titanium dioxide nanobelts;
[0115] (2) Add rhenium chloride, cerium nitrate and ammonium metavanadate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of rhenium to titanium dioxide nanobelts is 0.5:100 based on rhenium in rhenium chloride; the mass ratio of cerium nitrate to titanium dioxide nanobelts is 1:100 based on cerium in cerium nitrate; and the mass ratio of vanadium to titanium dioxide nanobelts is 2:100 based on vanadium in ammonium metavanadate. Ultrasonic dispersion is performed for 2 h, and then the solvent is evaporated at 90°C to obtain a dry solid. The dry solid is calcined in air at a heating rate of 10°C / min to 550°C for 2 h to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0116] Example 3
[0117] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component. The titanium dioxide nanobelts are doped with auxiliary cerium, auxiliary zinc and auxiliary chromium. The mass ratio of auxiliary cerium to titanium dioxide nanobelts is 1:100, the mass ratio of auxiliary zinc to titanium dioxide nanobelts is 2:100, and the mass ratio of auxiliary chromium to titanium dioxide nanobelts is 1:100.
[0118] The titanium-based catalyst preparation method comprises the following steps:
[0119] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0120] (1.1) Mix 0.2 mol of titanyl sulfate and 500 mL of 15 M NaOH solution, transfer to a hydrothermal kettle with a liner, place the hydrothermal kettle in an oven, and heat at 140 °C for 72 h. After the hydrothermal reaction is completed, remove the residual NaOH solution by filtration to obtain a white sodium titanate solid.
[0121] (1.2) Place the white sodium titanate solid in a 0.1 M HCl solution containing 0.5 mol benzyl alcohol and stir for 6 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0122] (1.3) washing the titanate nanobelts with deionized water until the pH value is 4, then filtering, and then drying in an oven at 110°C to obtain a titanium dioxide nanobelt precursor;
[0123] (1.4) The titanium dioxide nanobelt precursor was calcined in air at 300°C for 4 h at a heating rate of 5°C / min; then the calcination atmosphere was changed to argon and calcined in argon at 550°C for 6 h at a heating rate of 10°C / min. After the calcination, the precursor was naturally cooled to room temperature to obtain titanium dioxide nanobelts;
[0124] (2) Add cerium nitrate, zinc nitrate and chromium nitrate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of cerium to titanium dioxide nanobelts is 1:100 based on cerium in cerium nitrate; the mass ratio of zinc to titanium dioxide nanobelts is 2:100 based on zinc in zinc nitrate; the mass ratio of chromium to titanium dioxide nanobelts is 1:100 based on chromium in chromium nitrate. Ultrasonic dispersion is performed for 2 h, and then the solvent is evaporated at 95°C to obtain a dry solid. The dry solid is heated to 400°C in air at a heating rate of 5°C / min and calcined for 4 h to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0125] Example 4
[0126] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component. The titanium dioxide nanobelts are doped with auxiliary molybdenum, auxiliary zinc and auxiliary vanadium, and the mass ratio of the auxiliary molybdenum to the titanium dioxide nanobelts is 3:100, the mass ratio of the auxiliary zinc to the titanium dioxide nanobelts is 1:100, and the mass ratio of the auxiliary vanadium to the titanium dioxide nanobelts is 1:100.
[0127] The titanium-based catalyst preparation method comprises the following steps:
[0128] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0129] (1.1) Mix 0.2 mol of titanium dioxide and 500 mL of 10 M NaOH solution, transfer to a hydrothermal kettle with an inner liner, place the hydrothermal kettle in an oven, and heat at 190 °C for 24 h. After the hydrothermal reaction is completed, filter out the residual NaOH solution to obtain a white sodium titanate solid.
[0130] (1.2) Place the white sodium titanate solid in a 5 M HCl solution containing 0.1 mol styrax alcohol and stir for 4 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0131] (1.3) washing the titanate nanobelts with deionized water until the pH value is 6, then filtering, and then drying in an oven at 100°C to obtain a titanium dioxide nanobelt precursor;
[0132] (1.4) calcining the titanate nanobelts at 250°C in air at a heating rate of 5°C / min for 4 h; then changing the calcination atmosphere to argon and calcining at 650°C in argon at a rate of 10°C / min for 5 h. After the calcination, the nanobelts were naturally cooled to room temperature to obtain titanium dioxide nanobelts;
[0133] (2) Add ammonium molybdate tetrahydrate, zinc nitrate and ammonium metavanadate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of molybdenum to titanium dioxide nanobelts is 3:100 based on the molybdenum in ammonium molybdate tetrahydrate; the mass ratio of zinc to titanium dioxide nanobelts is 1:100 based on the zinc in zinc nitrate; and the mass ratio of vanadium to titanium dioxide nanobelts is 1:100 based on the vanadium in ammonium metavanadate. Ultrasonic dispersion is performed for 2 h, and then the solvent is evaporated at 100°C to obtain a dry solid. The dry solid is heated to 600°C in air at a heating rate of 10°C / min and calcined for 2 h to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0134] Example 5
[0135] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component. The titanium dioxide nanobelts are doped with auxiliary agents rhenium, auxiliary agent chromium and auxiliary agent vanadium, and the mass ratio of the auxiliary agent rhenium to the titanium dioxide nanobelts is 0.5:100, the mass ratio of the auxiliary agent chromium to the titanium dioxide nanobelts is 1:100, and the mass ratio of the auxiliary agent vanadium to the titanium dioxide nanobelts is 3:100.
[0136] The titanium-based catalyst preparation method comprises the following steps:
[0137] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0138] (1.1) Mix 0.2 mol of titanium dioxide and 500 mL of 20 M NaOH solution, transfer to a hydrothermal kettle with a liner, place the hydrothermal kettle in an oven, and heat at 120 °C for 96 h. After the hydrothermal reaction is completed, filter out the residual NaOH solution to obtain a white sodium titanate solid;
[0139] (1.2) Place the white sodium titanate solid in a 0.5 M HCl solution containing 0.02 mol cinnamyl alcohol and stir for 4 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0140] (1.3) washing the titanate nanobelts with deionized water until the pH value is 7, then filtering, and then drying in an oven at 120°C to obtain a titanium dioxide nanobelt precursor;
[0141] (1.4) calcining the titanium dioxide nanobelt precursor at 450°C in air for 4 h at a heating rate of 15°C / min; then changing the calcination atmosphere to argon and calcining at 700°C in argon for 3 h at a heating rate of 10°C / min; after calcination, naturally cooling to room temperature to obtain titanium dioxide nanobelts;
[0142] (2) Add rhenium chloride, chromium nitrate and ammonium metavanadate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of rhenium to titanium dioxide nanobelts is 0.5:100 based on rhenium in rhenium chloride, the mass ratio of chromium to titanium dioxide nanobelts is 1:100 based on chromium in chromium nitrate, and the mass ratio of vanadium to titanium dioxide nanobelts is 3:100 based on vanadium in ammonium metavanadate. Ultrasonic dispersion is performed for 1 h, and then the solvent is evaporated at 80°C to obtain a dry solid. The dry solid is heated to 300°C in air at a heating rate of 5°C / min and calcined for 4 h to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0143] Example 6
[0144] The present embodiment provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component, and the titanium dioxide nanobelts are doped with auxiliary ruthenium, auxiliary chromium and auxiliary zinc, and the mass ratio of auxiliary ruthenium to titanium dioxide nanobelts is 0.5:100, the mass ratio of auxiliary chromium to titanium dioxide nanobelts is 1:100, and the mass ratio of auxiliary zinc to titanium dioxide nanobelts is 3:100.
[0145] The titanium-based catalyst preparation method comprises the following steps:
[0146] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0147] (1.1) Mix 0.2 mol of P25 titanium dioxide powder and 500 mL of 1 M NaOH solution, transfer the mixture to a hydrothermal kettle with an inner liner, place the kettle in an oven, and heat at 200 °C for 12 h to perform a hydrothermal reaction. After the hydrothermal reaction is completed, remove the residual NaOH solution by filtration to obtain a white sodium titanate solid.
[0148] (1.2) Place the white sodium titanate solid in 0.1 M HNO 3 The solution was stirred for 6 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0149] (1.3) washing the titanate nanobelts with deionized water until the pH value is 5, then filtering, and then drying in an oven at 90°C to obtain a titanium dioxide nanobelt precursor;
[0150] (1.4) calcining the titanium dioxide nanobelt precursor at 400°C in air at a heating rate of 5°C / min for 3 h, then changing the calcination atmosphere to argon and calcining at 500°C in argon at a heating rate of 5°C / min for 6 h; after calcination, naturally cooling to room temperature to obtain titanium dioxide nanobelts;
[0151] (2) Add ruthenium chloride, chromium acetate and zinc nitrate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of ruthenium to titanium dioxide nanobelts is 0.5:100 based on ruthenium in ruthenium chloride; the mass ratio of chromium to titanium dioxide nanobelts is 1:100 based on chromium in chromium acetate; the mass ratio of zinc to titanium dioxide nanobelts is 3:100 based on zinc in zinc nitrate. Ultrasonic dispersion for 1 h, then evaporate and remove the solvent at 90°C to obtain a dry solid. The dry solid is heated to 400°C in air at a heating rate of 5°C / min and calcined for 2 h to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0152] Example 7
[0153] The difference between this embodiment and embodiment 1 is that in step (1.2), the amount of 2-phenylisopropanol used is 0.02 mol, and in step (1.4), calcination is performed in air at 300°C for 2 h, and then calcination is performed in argon at 500°C for 2 h.
[0154] Example 8
[0155] The difference between this embodiment and embodiment 1 is that in step (1.2), the amount of 2-phenylisopropanol used is 2 mol, and in step (1.4), calcination is performed in air at 450°C for 3 h, and then calcination is performed in argon at 650°C for 5 h.
[0156] Example 9
[0157] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of rhenium to titanium dioxide nanobelts is 0.1:100 based on rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 0.2:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 0.2:100 based on molybdenum in ammonium molybdate tetrahydrate.
[0158] Example 10
[0159] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of rhenium to titanium dioxide nanobelts is 2:100 based on rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 1:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 2:100 based on molybdenum in ammonium molybdate tetrahydrate.
[0160] Embodiment 11
[0161] The difference between this embodiment and embodiment 1 is that only rhenium chloride is added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 0.5:100 based on the rhenium in rhenium chloride.
[0162] Example 12
[0163] The difference between this embodiment and embodiment 1 is that only rhenium chloride is added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 5:100 based on the rhenium in rhenium chloride.
[0164] Example 13
[0165] The difference between this embodiment and embodiment 1 is that only ruthenium chloride is added in step (2), and the mass ratio of ruthenium to titanium dioxide nanobelts is 0.5:100 based on the ruthenium in ruthenium chloride.
[0166] Embodiment 14
[0167] The difference between this embodiment and embodiment 1 is that only ruthenium chloride is added in step (2), and the mass ratio of ruthenium to titanium dioxide nanobelts is 5:100 based on the ruthenium in ruthenium chloride.
[0168] Embodiment 15
[0169] The difference between this embodiment and embodiment 1 is that only ammonium molybdate tetrahydrate is added in step (2), and the mass ratio of molybdenum to titanium dioxide nanobelts is 0.5:100 based on the molybdenum in ammonium molybdate tetrahydrate.
[0170] Example 16
[0171] The difference between this embodiment and embodiment 1 is that only ammonium molybdate tetrahydrate is added in step (2), and the mass ratio of molybdenum to titanium dioxide nanobelts is 5:100 based on the molybdenum in ammonium molybdate tetrahydrate.
[0172] Embodiment 17
[0173] The difference between this embodiment and embodiment 1 is that only ammonium metavanadate is added in step (2), and the mass ratio of vanadium to titanium dioxide nanobelts is 0.5:100 based on the vanadium in the ammonium metavanadate.
[0174] Embodiment 18
[0175] The difference between this embodiment and embodiment 1 is that only ammonium metavanadate is added in step (2), and the mass ratio of vanadium to titanium dioxide nanobelts is 5:100 based on the vanadium in the ammonium metavanadate.
[0176] Embodiment 19
[0177] The difference between this embodiment and embodiment 1 is that only cerium nitrate is added in step (2), and the mass ratio of cerium to titanium dioxide nanobelts is 0.5:100 based on the cerium in the cerium nitrate.
[0178] Embodiment 20
[0179] The difference between this embodiment and embodiment 1 is that only cerium nitrate is added in step (2), and the mass ratio of cerium to titanium dioxide nanobelts is 5:100 based on the cerium in the cerium nitrate.
[0180] Embodiment 21
[0181] The difference between this embodiment and embodiment 1 is that only zinc nitrate is added in step (2), and the mass ratio of zinc to titanium dioxide nanobelts is 0.5:100 based on the zinc in the zinc nitrate.
[0182] Embodiment 22
[0183] The difference between this embodiment and embodiment 1 is that only zinc nitrate is added in step (2), and the mass ratio of zinc to titanium dioxide nanobelts is 5:100 based on the zinc in the zinc nitrate.
[0184] Embodiment 23
[0185] The difference between this embodiment and embodiment 1 is that only chromium nitrate is added in step (2), and the mass ratio of chromium to titanium dioxide nanobelts is 0.5:100 based on the chromium in the chromium nitrate.
[0186] Embodiment 24
[0187] The difference between this embodiment and embodiment 1 is that only chromium nitrate is added in step (2), and the mass ratio of chromium to titanium dioxide nanobelts is 5:100 based on the chromium in the chromium nitrate.
[0188] Embodiment 25
[0189] The difference between this embodiment and embodiment 1 is that rhenium chloride and ruthenium chloride are added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 2:100 based on the rhenium in rhenium chloride; and the mass ratio of ruthenium to titanium dioxide nanobelts is 2:100 based on the ruthenium in ruthenium chloride.
[0190] Embodiment 26
[0191] The difference between this embodiment and embodiment 1 is that rhenium chloride, ruthenium chloride, ammonium molybdate tetrahydrate and ammonium metavanadate are added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 1:100 based on the rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 1:100 based on the ruthenium in ruthenium chloride; the mass ratio of molybdenum to titanium dioxide nanobelts is 1:100 based on the molybdenum in ammonium molybdate tetrahydrate; and the mass ratio of vanadium to titanium dioxide nanobelts is 1:100 based on the vanadium in ammonium metavanadate.
[0192] Embodiment 27
[0193] The difference between this embodiment and embodiment 1 is that rhenium chloride, ruthenium chloride, ammonium molybdate tetrahydrate, ammonium metavanadate and cerium nitrate are added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelt is 0.5:100 based on the rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelt is 0.5:100 based on the ruthenium in ruthenium chloride; the mass ratio of molybdenum to titanium dioxide nanobelt is 1:100 based on the molybdenum in ammonium molybdate tetrahydrate; the mass ratio of vanadium to titanium dioxide nanobelt is 1:100 based on the vanadium in ammonium metavanadate; and the mass ratio of cerium to titanium dioxide nanobelt is 1:100 based on the cerium in cerium nitrate.
[0194] Embodiment 28
[0195] The difference between this embodiment and embodiment 1 is that rhenium chloride, ruthenium chloride, ammonium molybdate tetrahydrate, ammonium metavanadate, cerium nitrate and zinc nitrate are added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelt is 0.5:100 based on the rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelt is 0.5:100 based on the ruthenium in ruthenium chloride; the mass ratio of molybdenum to titanium dioxide nanobelt is 0.5:100 based on the molybdenum in ammonium molybdate tetrahydrate; the mass ratio of vanadium to titanium dioxide nanobelt is 0.5:100 based on the vanadium in ammonium metavanadate; the mass ratio of cerium to titanium dioxide nanobelt is 1:100 based on the cerium in cerium nitrate; and the mass ratio of zinc to titanium dioxide nanobelt is 1:100 based on the zinc in zinc nitrate.
[0196] Embodiment 29
[0197] The difference between this embodiment and embodiment 1 is that rhenium chloride, ruthenium chloride, ammonium molybdate tetrahydrate, ammonium metavanadate, cerium nitrate, zinc nitrate and chromium nitrate are added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelt is 0.5:100 based on the rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelt is 0.5:100 based on the ruthenium in ruthenium chloride; the mass ratio of molybdenum to titanium dioxide nanobelt is 0.5:100 based on the molybdenum in ammonium molybdate tetrahydrate; the mass ratio of vanadium to titanium dioxide nanobelt is 0.5:100 based on the vanadium in ammonium metavanadate; the mass ratio of cerium to titanium dioxide nanobelt is 0.5:100 based on the cerium in cerium nitrate; the mass ratio of zinc to titanium dioxide nanobelt is 0.5:100 based on the zinc in zinc nitrate; the mass ratio of chromium to titanium dioxide nanobelt is 1:100 based on the chromium in chromium nitrate.
[0198] Embodiment 30
[0199] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of rhenium to titanium dioxide nanobelts is 0.05:100 based on rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 0.05:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 0.1:100 based on molybdenum in ammonium molybdate tetrahydrate.
[0200] Embodiment 31
[0201] The difference between this embodiment and embodiment 1 is that in step (2), the mass ratio of rhenium to titanium dioxide nanobelts is 3:100 based on rhenium in rhenium chloride; the mass ratio of ruthenium to titanium dioxide nanobelts is 3:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 2:100 based on molybdenum in ammonium molybdate tetrahydrate.
[0202] Embodiment 32
[0203] The difference between this embodiment and embodiment 1 is that only rhenium chloride is added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 0.2:100 based on the rhenium in rhenium chloride.
[0204] Embodiment 33
[0205] The difference between this embodiment and embodiment 1 is that only rhenium chloride is added in step (2), and the mass ratio of rhenium to titanium dioxide nanobelts is 8:100 based on the rhenium in rhenium chloride.
[0206] Comparative Example 1
[0207] This comparative example provides a titanium-based catalyst, which includes titanium dioxide nanobelts with oxygen vacancy defects as the main active component, and the titanium dioxide nanobelts are doped with auxiliary agents rhenium, auxiliary agent ruthenium and auxiliary agent molybdenum, and the mass ratio of the auxiliary agent rhenium to the titanium dioxide nanobelts is 0.5:100, the mass ratio of the auxiliary agent ruthenium to the titanium dioxide nanobelts is 1:100, and the mass ratio of the auxiliary agent molybdenum to the titanium dioxide nanobelts is 2:100.
[0208] The titanium-based catalyst preparation method comprises the following steps:
[0209] (1) Preparation of titanium dioxide nanobelts with oxygen vacancy defects
[0210] (1.1) Mix 0.2 mol of P25 titanium dioxide powder and 500 mL of 8 M NaOH solution, transfer the mixture to a hydrothermal kettle with an inner liner, place the kettle in an oven, and heat at 160 °C for 36 h to perform a hydrothermal reaction. After the hydrothermal reaction is completed, remove the residual NaOH solution by filtration to obtain a white sodium titanate solid.
[0211] (1.2) Add the white sodium titanate solid to a 1M HCl solution containing 0.5 mol 2-phenylisopropanol and stir for 3 h to generate titanate nanobelts by alcohol-assisted ion exchange self-assembly;
[0212] (1.3) washing the titanate nanobelts with deionized water until the pH value is 5, then filtering, and then drying in an oven at 80°C to obtain a titanium dioxide nanobelt precursor;
[0213] (1.4) calcining the titanium dioxide nanobelt precursor at 600°C in air for 4 h at a heating rate of 5°C / min, and naturally cooling to room temperature after calcination to obtain titanium dioxide nanobelts;
[0214] (2) Add rhenium chloride, ruthenium chloride, and ammonium molybdate tetrahydrate to a beaker and disperse and dissolve them in 200 mL of deionized water, then add titanium dioxide nanobelts, wherein the mass ratio of rhenium to titanium dioxide nanobelts is 0.5:100 based on rhenium in rhenium chloride, the mass ratio of ruthenium to titanium dioxide nanobelts is 1:100 based on ruthenium in ruthenium chloride; and the mass ratio of molybdenum to titanium dioxide nanobelts is 2:100 based on molybdenum in ammonium molybdate tetrahydrate. Ultrasonic dispersion for 1 hour, then evaporate and remove the solvent at 85°C to obtain a dry solid, and the dry solid is calcined in air at a heating rate of 5°C / min to 450°C for 3 hours to obtain a powdered titanium-based catalyst. The powdered titanium-based catalyst is simply pressed into tablets by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0215] Comparative Example 2
[0216] This comparative example provides a titanium-based catalyst, which is a titanium dioxide nanobelt with oxygen vacancy defects. The preparation method of the titanium-based catalyst comprises the following steps:
[0217] (1.1) Mix 0.2 mol of P25 titanium dioxide powder and 500 mL of 8 M NaOH solution, transfer the mixture to a hydrothermal kettle with an inner liner, place the hydrothermal kettle in an oven, and heat at 160 °C for 36 h. After the hydrothermal reaction is completed, filter out the residual NaOH solution to obtain a white sodium titanate solid.
[0218] (1.2) Place the white sodium titanate solid in a 1M HCl solution containing 0.5 mol 2-phenylisopropanol and stir for 3 h to perform alcohol-assisted ion exchange self-assembly to generate titanate nanobelts;
[0219] (1.3) washing the titanate nanobelts with deionized water until the pH value is 5, then filtering, and then drying in an oven at 80°C to obtain a titanium dioxide nanobelt precursor;
[0220] (1.4) The titanium dioxide nanobelt precursor was calcined in air at 350°C for 3 h at a heating rate of 5°C / min, and then the calcination atmosphere was changed to argon gas, and calcined in argon gas at 600°C for 4 h at a heating rate of 5°C / min. After the calcination, it was naturally cooled to room temperature to obtain titanium dioxide nanobelts. The titanium dioxide nanobelts were simply tableted by a tablet press and crushed into 20-40 meshes to obtain the aforementioned titanium-based catalyst.
[0221] Comparative Example 3
[0222] The difference between this embodiment and embodiment 1 is that in step (1.2), the amount of 2-phenylisopropanol used is 0.01 mol, and in step (1.4), calcination is performed in air at 300°C for 2 h, and then calcination is performed in argon at 500°C for 1 h.
[0223] Comparative Example 4
[0224] The difference between this embodiment and embodiment 1 is that in step (1.2), the amount of 2-phenylisopropanol used is 2 mol, and in step (1.4), calcination is carried out in air at 450°C for 4 h and then in argon at 700°C for 6 h.
[0225] Test Example 1
[0226] The titanium dioxide nanobelts obtained in Example 1 were subjected to SEM testing. Figure 1 As shown, from Figure 1 It can be seen that the width of the titanium dioxide nanoribbons is between 80 and 120 nm.
[0227] The titanium dioxide nanobelts obtained in Example 1 were subjected to TEM test. The results are as follows Figure 2 As shown, from Figure 2 It can be seen that the titanium dioxide nanobelts have uniform morphology and the length of the nanobelts can reach several microns.
[0228] Test Example 2
[0229] The oxygen vacancy defect concentration of the titanium dioxide nanobelts having oxygen vacancy defects provided in the above examples and comparative examples was measured, and the results are shown in Table 1 below.
[0230] 20 g of the titanium-based catalyst provided in the above examples and comparative examples were respectively filled in a fixed bed reactor, the reaction bed was heated to 50° C., and the sulfide intermediate ( ) acetonitrile solution (the mass ratio of acetonitrile to sulfide intermediate is 3:1) is introduced into the fixed bed at a rate of 0.5 g / min, and a hydrogen peroxide solution (mass concentration is 50wt%) is introduced into the fixed bed at a rate of 0.1 g / min for continuous oxidation to obtain sulfonepyraclostrobin, and the reaction product is detected by liquid chromatography. The oxygen vacancy defect concentration, the conversion rate of sulfide intermediates, the selectivity of sulfonepyraclostrobin and the thickness of titanium dioxide nanobelts are measured, and the results are shown in Table 1.
[0231] 1. The method for determining the concentration of oxygen vacancy defects in titanium dioxide nanobelts is as follows: using thionine (TH) as a titrant, the surface oxygen vacancy concentration is determined by electronic titration. 10 mg of titanium dioxide nanobelts is suspended in 10 mL of deionized water, then added to 2 mL of thionine aqueous solution (0.1 mM), the suspension is filtered and the UV-visible absorption spectrum of the filtrate is quickly measured at 602.5 nm. Assuming that one oxygen vacancy (V o ) site is accompanied by two Ti 3+ (Ti 3+ -V o -Ti 3+ ), the titration principle is as follows: TH exists as a dark blue monovalent cation and is reduced to a colorless anion (TH) in two steps. 2- ) form, the oxygen vacancy defect concentration in titanium dioxide nanoribbons can be calculated based on this electronic titration method.
[0232] 2Ti 3+ + 2TH(blue) → 2Ti 4+ +2TH - (1)
[0233] 2TH - =TH 2-( Colorless) + TH (2)
[0234] 2. The calculation method of the conversion rate of thioether intermediates is:
[0235] Conversion rate (%) = (1-remaining moles of sulfide intermediate / input moles of sulfide intermediate) × 100.
[0236] 3. The calculation method of the selectivity of sulfonepyraclostrobin is:
[0237] Selectivity (%) = [molar concentration of sulfonepyraclostrobin / (molar concentration of sulfonepyraclostrobin) + (molar concentration of other products)] × 100.
[0238] 4. The thickness of the titanium dioxide nanoribbons was measured using atomic force microscopy.
[0239] Table 1
[0240]
[0241] It can be seen from the experimental results of Examples 1-8 and Comparative Examples 3-4 that when the main active component of the titanium-based catalyst is titanium dioxide nanobelts, and the concentration of oxygen vacancy defects in the titanium dioxide nanobelts is 5-20 μmol / g, the titanium-based catalyst is used in a fixed bed for continuous oxidation of sulfide intermediates to synthesize sulfonepyrazoline, and the conversion rate of sulfide intermediates reaches 100%, and the selectivity of sulfonepyrazoline is high. When the concentration of oxygen vacancy defects is too small, the number of surface defect sites is too small, which is not conducive to the adsorption and activation of the reactants, thereby significantly reducing the selectivity of sulfonepyrazoline; when the concentration of oxygen vacancy defects is too large, the adsorption capacity of the reactants is too strong, which is not conducive to product desorption, thereby causing the selectivity of sulfonepyrazoline to no longer increase, or even slightly decrease.
[0242] It can be seen from the experimental results of Example 1, Examples 9-29, and Comparative Example 2 that when the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelt is 0.5-5:100, regardless of whether the auxiliary metal component M is a single metal or multiple metals, such as the type of auxiliary metal M is one, two, three, four, five, six or seven, as long as the mass ratio of the total mass of the auxiliary metal to the titanium dioxide nanobelt is 0.5-5:100, the titanium-based catalyst is used in a fixed bed for the continuous oxidation of sulfide intermediates to synthesize sulfonepyrazoline, and the conversion rate of sulfide intermediates and the selectivity of sulfonepyrazoline are both excellent. It can be seen from the experimental results of Examples 30-33 and Comparative Example 2 that when the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelt is too small, the number of active sites is reduced due to the reduction in the auxiliary metal content, thereby reducing the selectivity of sulfonepyrazoline. When the auxiliary metal component M is not doped, the selectivity of sulfonepyrazoline is further reduced. When the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelts is too large, the auxiliary metal content increases, resulting in the selectivity of sulfonepyraclostrobin no longer increasing or even decreasing.
[0243] From the experimental results of Example 1 and Comparative Example 1, it can be seen that when the titanium dioxide nanobelt precursor is first calcined in an oxygen-containing atmosphere and then calcined in an inert atmosphere in step (1.4), the selectivity of sulfonepyraclostrobin is higher. When the calcination atmosphere is only an oxygen-containing atmosphere (air), the selectivity of sulfonepyraclostrobin is significantly reduced, indicating that calcination under two different atmospheres can further promote the oxygen vacancy defect (V o ) is formed, thereby improving the selectivity of sulfonepyraclostrobin.
[0244] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0245] The titanium-based catalyst provided in the present application is used to form oxygen vacancy defects (V o ) is the main active component, and the titanium dioxide nanobelt is doped with an auxiliary metal component M. Due to the loss of lattice oxygen in the titanium dioxide nanobelt, part of the tetravalent Ti 4+ Reducing to Ti 3+ , adjacent Ti 3+ With oxygen vacancies (V o ) formed between Ti 3+ -V o -Ti 3+ Surface defect sites. The titanium dioxide nanobelt has a large specific surface area and fully exposed active sites. In the reaction of sulfide oxidation to synthesize sulfone pyraclostrobin, the unsaturated Ti 3+ -V o -Ti 3+ Surface defect sites can enhance the adsorption and activation of reactants, and the adjacent Ti 3+ It can form stable Ti with sulfide and hydrogen peroxide 3+ -S-Ti 3+ and Ti 3+ -O-Ti 3+ The titanium dioxide nanobelts have good wettability and ductility, which helps the diffusion and transport of reactant molecules, thereby increasing the reaction rate.
[0246] In addition, due to Ti 3+ -V o -Ti 3+ Surface defect sites have higher energy, oxygen vacancies (V o ) can interact with the additive metal ions electronically, through Ti 3+ -V o -Ti 3+The electron positioning center formed by the surface defect sites anchors the auxiliary metal component M, improves the dispersibility and stability of the auxiliary metal component M on the titanium dioxide nanobelts, and thus provides more reaction active sites. At the same time, it also extends the service life of the titanium-based catalyst, which is beneficial to the efficient and stable oxidation of sulfide to sulfone in the reaction.
[0247] The titanium-based catalyst provided in the present application, in the reaction of using a fixed bed to oxidize a sulfide intermediate to synthesize sulfonepyraclostrobin, can achieve a raw material conversion rate of 100%, a high product selectivity, and also realize the continuous production of sulfonepyraclostrobin.
[0248] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A titanium-based catalyst, characterized in that include: A main active component and an auxiliary metal component M doped in the main active component; Among them, the main active component is titanium dioxide nanobelt, and the titanium dioxide nanobelt forms oxygen vacancy defects, and the concentration of the oxygen vacancy defects is 5~20μmol / g; the auxiliary metal component M includes at least one of Re, Ru, Mo, V, Ce, Zn and Cr.
2. The titanium-based catalyst according to claim 1, characterized in that In the titanium-based catalyst, the mass ratio of the auxiliary metal component M to the titanium dioxide nanobelt is 0.5-5:
100.
3. The titanium-based catalyst according to claim 1, characterized in that The titanium dioxide nanobelt is in the shape of a nanobelt and has a thickness of 1 to 5 nm.
4. A method for preparing a titanium-based catalyst according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: Step S1, preparing titanium dioxide nanobelts with oxygen vacancy defects; Step S2, mixing the titanium dioxide nanobelt, M source and water, and then sequentially performing a first drying and a first calcination to obtain a titanium-based catalyst.
5. The method for preparing a titanium-based catalyst according to claim 4, characterized in that: The step S1 comprises: Step S11, mixing a titanium source with an alkaline solution, and performing a hydrothermal reaction to obtain titanate; Step S12, mixing the titanate, alcohol and acidic solution to perform ion exchange to obtain titanate nanobelts; Step S13, washing and second drying the titanate nanobelts in sequence to obtain a titanium dioxide nanobelt precursor; Step S14, performing a second calcination on the titanium dioxide nanobelt precursor to obtain the titanium dioxide nanobelt.
6. The method for preparing a titanium-based catalyst according to claim 5, characterized in that: In the step S11, the titanium source is at least one of titanium dioxide, titanyl sulfate and P25 titanium dioxide; And / or, the alkaline solution includes sodium hydroxide solution and / or potassium hydroxide solution; And / or, the concentration of the alkaline solution is 1-20 mol / L; And / or, the molar ratio of the titanium source to the alkaline solution is 1:2-50; And / or, the temperature of the hydrothermal reaction is 120-200° C., and the time of the hydrothermal reaction is 12-96 hours.
7. The method for preparing a titanium-based catalyst according to claim 5, characterized in that: In step S12, the concentration of the acidic solution is 0.01-5 mol / L; And / or, the acidic solution includes hydrochloric acid solution and / or nitric acid solution; And / or, the alcohol is at least one of aromatic alcohols having 6 to 15 carbon atoms; And / or, the molar ratio of the alcohol to the titanium source is 0.1-10:
1.
8. The method for preparing a titanium-based catalyst according to claim 5, characterized in that: In the step S14, the second calcination includes first performing oxygen-containing calcination in an oxygen-containing atmosphere and then performing inert calcination in an inert atmosphere; wherein the oxygen-containing atmosphere includes air and / or oxygen; and the inert atmosphere includes argon and / or nitrogen.
9. The method for preparing a titanium-based catalyst according to claim 4, characterized in that: In the step S2, the temperature of the first calcination is 300-600° C., and the time of the first calcination is 2-4 hours; And / or, the M source includes at least one of a Re source, a Ru source, a Mo source, a V source, a Ce source, a Zn source and a Cr source; wherein the Re source is selected from at least one of rhenium chloride, perrhenic acid and ammonium perrhenate; the Ru source is selected from ruthenium chloride and / or ruthenium acetate; the Mo source is selected from at least one of ammonium molybdate tetrahydrate, molybdenum chloride, phosphomolybdic acid and ammonium phosphomolybdate; the V source is selected from ammonium metavanadate and / or vanadium trichloride; the Ce source is selected from at least one of cerium nitrate, cerium chloride, cerium sulfate and cerium acetate; the Zn source is selected from at least one of zinc nitrate, zinc chloride, zinc sulfate and zinc acetate; the Cr source is selected from at least one of chromium nitrate, chromium sulfate and chromium acetate.
10. A method for synthesizing sulfonepyraclostrobin, characterized in that: The synthesis method comprises: an oxidation reaction of a sulfide intermediate of formula (A) and hydrogen peroxide under the action of a catalyst to obtain the sulfonepyraclostrobin. The synthesis schematic diagram of the sulfonepyraclostrobin is as follows: ; Wherein, the catalyst is a titanium-based catalyst according to any one of claims 1 to 3 or a titanium-based catalyst obtained by the preparation method according to any one of claims 5 to 9; and the catalyst is loaded in a fixed bed.
Citation Information
Patent Citations
Anatase titanium dioxide nanocrystal containing single-electron-trapped oxygen vacancies and with exposed {001} face and preparation method thereof
CN103626225A
Anatase titanium dioxide nanoribbons exposing {010} crystal face and preparation method thereof
CN105347393A
Dimethyl sulfoxide preparation process based on photocatalyst
CN110698370A
Preparation method of pyroxasulfone
CN119143745A
Continuous preparation system and method of pyroxasulfone
CN119258947A
Cited By
Metal peroxide complex molecular catalyst, preparation method and application thereof, and continuous synthesis method of pyroxasulfone
CN120502363A